Experimental strategy of animal trial for the approval of anti-diabetic agents prior to their use in pre-human clinical trials (Bangladesh Journal of Pharmacology, 2015)
Although several naturally available drugs have been historically used for the treatment of diabetes mellitus throughout the world, few of them have been validated by scientific criteria. Before approval of any drug developed it should pass through animal trial prior to clinical human trial, which should followed by some standard ethical rules. Recently, a large diversity of animal models have been developed to better understand the pathogenesis of diabetes mellitus, and new drugs have been introduced in the market to treat this autoimmune disease. In the present article, we demonstrated some standard handling procedure of animal trial for the approval of anti-diabetic drug, which could be helpful for both academics and industrial scientific community to conduct the animal experiments. This research also contributes in the field of ethnopharmacology to design new strategies for the development of novel drugs to treat this serious condition of diabetes mellitus that constitutes a global public health.Video Clip of Methodology: Handling and caring of mice: 2 min 30 sec   Full Screen   AlternateInducing diabetes in mice and observing blood glucose level: 1 min 47 sec   Full Screen   AlternateDrug administration and observation of blood glucose level: 2 min 11 sec   Full Screen   Alternate